All Days 2018
DOI: 10.2118/193502-ms
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Heavy Oil Recovery Processes Using Hele-Shaw Cell

Abstract: The linear core flood (physical model) has been used severally in the past to conduct laboratory researches and experiments on Tertiary Oil Recovery. A potential pitfall of the 1D nature of the linear core flood arises during waterflooding; water channels would be blocked due to limited pathways, hence producing the additional oil before chemical consequently breaks through. In real reservoirs, there are more water pathways present; hence the relative impact of these chemical additives on incremental oil recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…A crucial observation in this system is that, compared to water injection, the oil recovery before breakthrough is reached by the formation of main fingers, which are subdivided into multiple little fingers. This observation has been reported in previous works [24][25][26], where the little sub-fingers lead to an increase in the contact area within the oil. The surfactant solution has a similar viscosity to water, but the formation of many small sub-fingers compared to the larger water fingers is evidence of the significantly lower IFT.…”
Section: Surfactant Flooding Testssupporting
confidence: 89%
“…A crucial observation in this system is that, compared to water injection, the oil recovery before breakthrough is reached by the formation of main fingers, which are subdivided into multiple little fingers. This observation has been reported in previous works [24][25][26], where the little sub-fingers lead to an increase in the contact area within the oil. The surfactant solution has a similar viscosity to water, but the formation of many small sub-fingers compared to the larger water fingers is evidence of the significantly lower IFT.…”
Section: Surfactant Flooding Testssupporting
confidence: 89%
“…[5,6,7,8,9,10]. [11] Udofia et al 2015 did some extensive works on ROBU cores to study the Multiphase Flow Transport Properties for Model Calibration. Their results show that measurements of drainage capillary pressure, resistivity index, spontaneous imbibition and relative permeability on ROBU cores follow same trend like other natural porous rocks in the literature when properly scaled and appear promising.…”
Section: Results Shows That At Elevated Temperature Of 73˚c Hengflo 6mentioning
confidence: 99%
“…for its validation Over the years, laboratory studies of Niger Delta Oil recovery by chemical slug were carried out by some researchers . [11,12,13,14,15,16,17,18,19,20,21,22,23,24,25] 2. EXPERIMENTAL…”
Section: Results Shows That At Elevated Temperature Of 73˚c Hengflo 6mentioning
confidence: 99%
“…Visual tests are more useful to identify the different processes occurring during chemical addition, whereas 2-D visual sandpack tests are extremely time-consuming , when testing multiple chemicals for comparative analysis; therefore, we adopted the Hele-Shaw-type experimentation due to practicality. Hele-Shaw flow is named after Hele-Shaw. , It has been shown that the fluid flow in porous media can be studied by Hele-Shaw cells, providing a convenient visualization of the subsurface process, of which has been widely applied for the said purpose. In this research, we studied different chemical additives and different injection strategies (chemicals are injected at the beginning, middle, and end of the steam injection process) to observe the flow characteristics of the steam and the growth of the steam chamber in the 2-D Hele-Shaw cell as they provide both rheological and displacementi.e., sweep capacity (chamber development and growth)as well as interfacial and chemical interaction (emulsification, reactions at the interface, wettability alteration, etc.) characteristics of the SAGD process.…”
Section: Introductionmentioning
confidence: 99%